2019
DOI: 10.1158/1078-0432.ccr-18-1390
|View full text |Cite
|
Sign up to set email alerts
|

Antibody–Fc/FcR Interaction on Macrophages as a Mechanism for Hyperprogressive Disease in Non–small Cell Lung Cancer Subsequent to PD-1/PD-L1 Blockade

Abstract: Hyperprogression (HP), a paradoxical boost in tumor growth, was described in a subset of patients treated with immune checkpoint inhibitors (ICI). Neither clinicopathologic features nor biological mechanisms associated with HP have been identified. Among 187 patients with non-small cell lung cancer (NSCLC) treated with ICI at our institute, cases with HP were identified according to clinical and radiologic criteria. Baseline histologic samples from patients treated with ICI were evaluated by IHC for myeloid an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
371
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 349 publications
(411 citation statements)
references
References 33 publications
14
371
3
3
Order By: Relevance
“…In summary, despite the numerous research teams that have documented HPD , the existence of this phenomenon remains a matter of dispute. Indeed, an analysis of the OAK trial , which was a randomized study of checkpoint blockade versus chemotherapy in lung cancer, did not show a difference in the number of “fast progressors” between the arms.…”
Section: Criteria For and Predictors Of Hpd According To Different Rementioning
confidence: 99%
See 2 more Smart Citations
“…In summary, despite the numerous research teams that have documented HPD , the existence of this phenomenon remains a matter of dispute. Indeed, an analysis of the OAK trial , which was a randomized study of checkpoint blockade versus chemotherapy in lung cancer, did not show a difference in the number of “fast progressors” between the arms.…”
Section: Criteria For and Predictors Of Hpd According To Different Rementioning
confidence: 99%
“…It is important to note, however, that using pre‐immunotherapy imaging may not always be feasible for all treatment settings; for example, in the first‐line setting not all cancer patients have pre‐immunotherapy scans available. Therefore, some groups (Table ) have suggested criteria for HPD that do not require pre‐ immunotherapy scans; these criteria will need to be validated in patients with existing pre‐immunotherapy scans. Recent data have shown that HPD can be recapitulated in preclinical models .…”
Section: Criteria For and Predictors Of Hpd According To Different Rementioning
confidence: 99%
See 1 more Smart Citation
“…One study has shown that MDM2 family amplification and epidermal growth factor receptor mutation may be associated with hyperprogression and poor clinical outcome . However, another study did not find any significant association in MDM2/4 amplification but argued that checkpoint inhibitors trigger Fc receptor in clustered epithelioid macrophages, leading to functional reprogramming toward a pro‐tumorigenic state leading to hyperprogression …”
Section: Discussionmentioning
confidence: 99%
“…9 However, another study did not find any significant association in MDM2/4 amplification but argued that checkpoint inhibitors trigger Fc receptor in clustered epithelioid macrophages, leading to functional reprogramming toward a pro-tumorigenic state leading to hyperprogression. 10 Literature on hyperprogression in HNSCC remains limited. In a retrospective study with 34 patients with recurrent and/or metastatic HNSCC, 29% of patients experienced hyperprogression based on a tumor growth kinetics ratio ≥2 based on pre-and postimmunotherapy imaging.…”
Section: Discussionmentioning
confidence: 99%